2001
DOI: 10.2337/diacare.24.6.989
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Miglitol Plus Metformin Combination Therapy in the Treatment of Type 2 Diabetes

Abstract: OBJECTIVE -To investigate the efficacy and safety of miglitol in combination with metformin in improving glycemic control in outpatients in whom type 2 diabetes is insufficiently controlled by diet alone.RESEARCH DESIGN AND METHODS -In this multicenter, double-blind, placebocontrolled study, 324 patients with type 2 diabetes were randomized, after an 8-week placebo run-in period, to treatment with either placebo, miglitol alone, metformin alone, or miglitol plus metformin for 36 weeks. The miglitol was titrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 26 publications
3
36
0
4
Order By: Relevance
“…a-Glucosidase inhibitors, such as acarbose and miglitol, slow the absorption of glucose by delaying digestion of starches in the small intestine (Chiasson and Naditch, 2001). Like viscous soluble fibers, these compounds reduce postprandial blood glucose and insulin excursions.…”
Section: Discussionmentioning
confidence: 99%
“…a-Glucosidase inhibitors, such as acarbose and miglitol, slow the absorption of glucose by delaying digestion of starches in the small intestine (Chiasson and Naditch, 2001). Like viscous soluble fibers, these compounds reduce postprandial blood glucose and insulin excursions.…”
Section: Discussionmentioning
confidence: 99%
“…20,[46][47][48] A one-year study demonstrated equivalent antihyperglycaemic efficacy with a metformin-sulphonylurea combination compared with a pioglitazone-sulphonylurea combination in patients inadequately controlled on a sulphonylurea alone. 49 The Rosiglitazone Evaluated for Cardiac Outcomes and Regulation of Glycaemia in Diabetes (RECORD) study demonstrated a greater reduction of HbA 1C with metformin (n=272) compared with rosiglitazone (n=301), when added to maximal sulphonylurea therapy for 18 months (mean treatment difference 0.06% [95% CI -0.09 to 0.20]).…”
Section: Metformin In Combinationmentioning
confidence: 99%
“…[18][19] Metformin has shown greater antihyperglycaemic efficacy than α-glucosidase inhibitors [20][21][22] and DPP-4 inhibitors [23][24] when given as monotherapy.…”
Section: Comparison With Other Oral Antidiabetic Agentsmentioning
confidence: 99%
“…glibenclamide [14] . In case of allopathy, results of clinical trials have shown that combination therapy with miglitol and metformin was found to be more effective than the use of single drug alone [15] . Establishment of standard quality control profile in global context to confirm the validity and reproducibility of phytochemical constituents in the form of processed extract rather than single isolated compound; proper analytical and spectroscopic method development for structural characterizations in combined forms; rigorous validation of safety profile and pharmacokinetic parameters is essential to find a scientific basic of phytosynergy which may give rise to a new generation of medicinal products -phyto-pharmaceuticals [11] .…”
Section: Phytosynergy In Type 2 Diabetesmentioning
confidence: 99%
“…Medicine in recent times, whether western classical or phyto-therapy, advocates for combination therapy, instead of single approach. Synergy research in phytotherapy, with the aid of "omics technologies" needs a rationale for establishing its pharmacological and therapeutic superiority to treat diseases which have hitherto been treated using synthetic drugs alone [11][12][13][14][15] . Along with the paradigm of translational health research with the perspectives of bench to bedside approach; all pharmaceutical RDs target to develop robust, cost effective, enhanced throughput in vitro assays which may be extrapolated to humans and serve the purpose of bio-waiver.…”
Section: Introductionmentioning
confidence: 99%